Analysis of Entrepreneurship Potential in Batak Women for Developing Toba Lake Tourism - Manurung, Ria; Ismail, Rizabuana; Munthe, Hadriana Marhaeni (Universitas Muhammadiyah Surakarta, 2019)
Optimizing the role of women in the development of tourism at this time is needed. This fact is based on the lack of women’s role in the public sphere. This is because there are still many people who adhere to the patriarchal principle so that the role of women is limited to domestic space. All aspects have such a perception, especially in the development of tourism activities, the role of women is still small and even invisible. Women are only seen participating in trading food or accessories to fulfill their daily needs. Including women as one of the main actors in the development of tourism is not impossible if the potential possessed by women can be developed. The study was conducted using a qualitative-quantitative approach using a questionnaire method to 75 respondents, in-depth interviews, non-participant observation, PRA, and discussion group elements in three districts namely Samosir District, Dairi District, and Toba Samosir District. The results of the study found data that Batak ethnic women who were in this research location had a lot of potential and abilities both in terms of ideas and creativity but were not yet able to develop them. The idea that informants have is not only to increase their economic needs but also to increase tourist arrivals in the Lake Toba tourism area. Besides, it was found that the Batak ethnic women were very active and would make every effort to meet the economic needs of their families. Toba Batak women want to have their own business but they still have obstacles in starting capital. The potential of Batak women in the field of technology is still not maximal, Toba Batak women do not use technological developments to develop their abilities and businesses.